Relationships between the rules and the way of struggle applied by top world male judoists - Boguszewski, D. (Archives of Budo, 2011)
Background and study aim. Refereeing rules were changed many times (in 2006, 2009, 2010). In 2006 liberalized the interpretations of the rules concerned penalties and edge situations. In 2009 made the golden score fight shorter and forbidden of the grip for the trousers. That grip was punished "shido". From 2010 referee must disqualify contestant who grips below the belt. The aim of this study was way of struggle top world judoists depend of refereeing rules. Material and methods. Method of measurement struggle dynamics by Kalina was used. The ratio of the number of effective events to all events in given category is the measure of those struggle components (category). Indices describes struggle dynamics are: AI -activity index, EA - index of effective offensive actions, EC - index of effective counterattacks, ED - index of effective defensive actions, SDI - global index of struggle dynamics. Detailed analysis was made according to Kodokan Judo order. Research material was recordings of 40 gold medal contests from top world judo tournaments in 2005, 2008, 2009 and 2010. 72 top world judo male players from 32 countries were in research group. Results. Struggle dynamics components were similar between players from different weight categories. However there was a significant difference in terms of contestants` activity in the years 2005, 2008, 2009 and 2010. Systematically decreased effectiveness of attacks and increased effectiveness of defense from 2005. In 2010 judoists rarely used the sacrifice throws and more leg throws. Effectiveness of throws in each group did not exceed 10%. Decreased the most effective hand throws. Average time of contests gradually increased since 2005, every year. Number of "ippons" remained at the high level, but significantly increased the number of golden score fights. Conclusions. Despite the liberalization of the rules dynamics decreased (players rarely attack, the average time of contests has extended). Changes of refereeing rules should be come to increase struggle dynamics. It is necessary to examine what influences the attractiveness of judo contests as a show.